Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

BeautyQueen327

  • 3 years ago

solve for x: (2-e^x)(e^(x))=1

  • This Question is Closed
  1. jishan
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    2- e^x=1/ e^x 1/e^x + e^x-2=0 e^2x - 2e^x+1=0 apply (a-b)^2=a^2+b^2-2ab ( e^x-1)^2=0 e^x-1=0 e^x=1 e^x=e^0 x=0,0

  2. jishan
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    thankssssss

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy